2017
DOI: 10.1183/23120541.00094-2016
|View full text |Cite
|
Sign up to set email alerts
|

Cooking fuel and respiratory symptoms among people living with HIV in rural Uganda

Abstract: Household air pollution (HAP) and chronic HIV infection are each associated with significant respiratory morbidity. Little is known about relationships between HAP and respiratory symptoms among people living with HIV. The objective of this study was to investigate the relationship between cooking fuel type and chronic respiratory symptoms in study participants from the Uganda AIDS Rural Treatment Outcomes Study.Study participants were enrolled at the time of antiretroviral therapy initiation and seen quarterl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Finally, we also found that having an adequately ventilated kitchen had an independent, inverse association with probable dementia. Air pollution is a growing problem globally [17] and has been linked, in studies from Uganda, to other health problems like respiratory symptoms [18,19]. One population-based study from Taiwan found that higher levels of carbon monoxide exposure were significantly associated with an increased risk of dementia [20].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we also found that having an adequately ventilated kitchen had an independent, inverse association with probable dementia. Air pollution is a growing problem globally [17] and has been linked, in studies from Uganda, to other health problems like respiratory symptoms [18,19]. One population-based study from Taiwan found that higher levels of carbon monoxide exposure were significantly associated with an increased risk of dementia [20].…”
Section: Discussionmentioning
confidence: 99%
“…Second, we acknowledge that the results should only be generalized to rural East African populations, characterized by subsistence farming, and high rates of food insecurity and biomass cooking fuel exposure. 58,59 Third, since many potentially important factors, including data on specific comorbidities, alcohol consumption, waist circumference, and adipose tissue parameters, were not included in the regression analyses, we are unable to rule out confounding by these factors. Further, we did not perform duplicate testing of inflammatory assays.…”
Section: Limitationsmentioning
confidence: 99%
“…Finally, we also found that having an adequately ventilated kitchen had an independent, inverse association with probable dementia. Air pollution is a growing problem globally (17) and has been linked, in studies from Uganda, to other health problems like respiratory symptoms (18,19). One population-based study from Taiwan found that higher levels of carbon monoxide exposure were significantly associated with increased risk of dementia (20).…”
Section: Discussionmentioning
confidence: 99%